INTERNATIONAL POLITICS OF GAY RIGHTS AND NIGERIA’S SAME SEX MARRIAGE (PROHIBITION ACT) 2014 - Udumaga, Cornel Chinedu U.; Ohams, Chinedu Graham; Ebiziem, Jude Ebiziem (African Journal of Social and Behavioural Sciences, 2021)
The confusion underlying the concept of International Human Right practices and the powers of a sovereign state to legislate for its citizens is under serious investigation. More so the international pressure mounted on developing countries to decriminalize gay practice seems as if it has taken a centre stage above hunger, disease and other social problems ravaging the world. The general debate on why some persons have the inclination for same sex affection, whether it is biological (genetic) or social (orientation) is less of our concern here, but the priority accorded it by governments have attracted the great debt on the gay rights. Incidentally Scholars have paid little or no attention on whether the municipal laws of developing countries violate the gay rights. We therefore, interrogate this observed gap in literature with this research question: Does Nigeria‟s Same Sex Marriage (Prohibition) Act 2014 violate international human right law? The study anchored on theory of rights by Harold Laski and employed ex-post-facto research design. Data for the study were sourced from official documents, books, journals, magazines, newspapers and internet materials. The data were analyzed using qualitative method. The study revealed that: the Same Sex Marriage Prohibition Act 2014 did not violate any known international human right practices. The study therefore, recommends that Nigeria should uphold the law, choose her friends and maintain the balance in interdependency.